Observation of electroweak production of a same-sign W boson pair in association with two jets in pp collisions at √s = 13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; et al. (Physical review letters, 2019)
This Letter presents the observation and measurement of electroweak production of a same-sign W boson pair in association with two jets using 36.1 fb−1 of proton-proton collision data recorded at a center-of-mass energy of √s=13 TeV by the ATLAS detector at the Large Hadron Collider. The analysis is performed in the detector fiducial phase-space region, defined by the presence of two same-sign leptons, electron or muon, and at least two jets with a large invariant mass and rapidity difference. A total of 122 candidate events are observed for a background expectation of 69±7 events, corresponding to an observed signal significance of 6.5 standard deviations. The measured fiducial signal cross section is σfid=2.89+0.51−0.48(stat)+0.29−0.28(syst) fb.